Wayang Kulit Show, Layar Tancap (Traveling Cinema Show), and History of Pre-Cinema - Imanjaya, Ekky (Journal of Art, Film, Television, Animation, Games and Technology, 2024)
This article will investigate that Javanese and Balinese Wayang Kulit Performance should be considered a legitimate  "grandfather" of modern cinema—especially in the archaeology of projection and screen. The author will apply Castle's Phantasmagoria and Manovich's Archaeology of the screen as the analysis tools. The paper will also examine direct connections between Wayang Kulit Show and contemporary cinema, particularly Layar tancap (traveling cinema), which emerged in the late 1890s in Southeast Asia Furthermore, finally, the paper will investigate to what extent the tradition of the Wayang show and its apparatus has influenced some of  Indonesia's as well as Malaysia’s terms of modern cinema to  Indonesia's  Layar tancap (traveling cinema). This research is in the same spirit as Thomas Elsaesser's proposal about the new way to reconstruct film history, moreover, consider expanding the pre-history cinema to Indonesia's shadow puppetry and putting Layar tancap as part of the global non-theatrical exhibition culture.